Narratives on becoming : identity and lifelong learning - Leaderman, Emilie Clucas; Jefferson, Jennifer S.; Gammel, Jo Ann; Motulsky, Sue; Rutstein-Riley, Amy (I am what I become: Constructing identities as lifelong learners, 2021)
"Learning and identity development are lifetime processes of becoming. The construction of self, of interest to scholars and practitioners in adult development and adult learning, is an ongoing process, with the self both forming and being formed by lived experience in privileged and oppressive contexts. Intersecting identities and the power dynamics within them shape how learners define themselves and others and how they make meaning of their experiences in the world. The series, I Am What I Become: Constructing Identities as Lifelong Learners, is an insightful and diverse collection of empirical research and narrative essays in identity development, adult development, and adult learning. The purpose of this series is to publish contributions that highlight the intimate and intricate connections between learning and identity. The series aims to assist our readers to understand and nurture adults who are always in the process of becoming. We hope to promote reflection and research at the intersection of identity and adult learning at any point across the adult lifespan. The rich array of qualitative research designs as well as autobiographic and narrative essays transform and expand our understanding of the lived experience of people both like us and unlike us, from the U.S. and beyond. Narratives on Becoming: Identity and Lifelong Learning, Volume Three of the series, explores a myriad of ways that authors' personal and professional growth has influenced identity development. These chapters provide insights into the intersectional identities and learning of writers. Drawing from the multiple paths that comprise the journey of lifelong learning, these authors present powerful stories that identify the ways relationships, environments, culture, travel, and values shape their identities, use literacy, teaching, and learning as vehicles for experimenting with new identities, negotiate multiple identities, contexts, and transitions involved in becoming, and construct meaning. Through their narrative essays and ethnographic/autobiographical accounts, the authors in this volume illuminate the power of transformational learning during life-changing events and transitions"--